To find the solution for the system of equations represented in Jian's table, we need to look for a pair of (x, y) values that satisfy both equations:
- \( y = 2x - 5 \)
- \( y = x - 3 \)
From the table:
-
For \( x = 0 \):
- \( y = 2(0) - 5 = -5 \)
- \( y = 0 - 3 = -3 \)
-
For \( x = 1 \):
- \( y = 2(1) - 5 = -3 \)
- \( y = 1 - 3 = -2 \)
-
For \( x = 2 \):
- \( y = 2(2) - 5 = -1 \)
- \( y = 2 - 3 = -1 \)
-
For \( x = 3 \):
- \( y = 2(3) - 5 = 1 \)
- \( y = 3 - 3 = 0 \)
Looking at the results, the only point where the y-values from both equations are equal in the table is at \( (2, -1) \).
Thus, the solution for the system of equations is:
(2, −1).